Body esteem, body mass index and risk for disordered eating among french elite adolescents engaged in synchronised swimming - Magnan, C.; Ferrand, C. (First international symposium sciences and practices in swimming, 2006)
The aim of the study was to examine body esteem, body mass Index and eating disorder Symptoms in competitive synchronised swimming adolescents and to compare these with athletes in non lean-sports and female College non-athletes. They completed Body Esteem Scale and the Eating Attitudes Test and the Body mass Index was computed. Results showed that the synchronised swimming athletes differed from the two other groups in Body Esteem-Attribution and Body Esteem-Appearance. Participants in the three groups did not differ on eating disorder attitudes. Regression analyses showed that body mass index and Body Esteem-Appearance accounted together for 41% of the variance in Dieting scores in the synchronised swimming athletes.